My first time: initiation into injecting drug use in Manipur and Nagaland, north-east India - Langkham Biangtung; Hocking Jane; Singh Bangkim; Longleng Verity; Kermode Michelle; Crofts Nick (BMC, 2007)
Abstract Background The north-east Indian states of Manipur and Nagaland are two of the six high HIV prevalence states in the country, and the main route of HIV transmission is injecting drug use. Understanding the pathways to injecting drug use can facilitate early intervention with HIV prevention programs. While several studies of initiation into injecting drug use have been conducted in developed countries, little is known about the situation in developing country settings. The aim of this study was to increase understanding of the contextual factors associated with initiation into injecting drug use in north-east India, and the influence of these factors on subsequent initiation of others. Method In mid 2006 a cross-sectional survey among 200 injecting drug users (IDUs) was undertaken in partnership with local NGOs that provide HIV prevention and care services and advocacy for IDUs in Imphal, Manipur and Dimapur, Nagaland. The questionnaire elicited detailed information about the circumstances of the first injection and the contexts of participants' lives. Demographic information, self-reported HIV status, and details about initiation of others were also recorded. Results Initiation into injecting drug use occurred at 20 years of age. The drugs most commonly injected were Spasmo-proxyvon (65.5%) and heroin (30.5%). In 53.5% cases, a needle belonging to someone else was used. Two-thirds (66.7%) had used the drug previously, and 91.0% had known other IDUs prior to initiation (mean = 7.5 others). The first injection was usually administered by another person (94.5%), mostly a friend (84.1%). Initiation is a social event; 98% had others present (mean = 2.7 others). Almost 70% of participants had initiated at least one other (mean = 5 others). Initiation of others was independently associated with being male and unemployed; having IDU friends and using alcohol around the time of initiation; and having been taught to inject and not paid for the drug at the time of initiation. Conclusion Targeting harm reduction messages to (non-injecting) drug users and capitalising on existing IDU social networks to promote safe injecting and deter initiation of others are possible strategies for reducing the impact of injecting drug use and the HIV epidemic in north-east India.